Anticancer activity of paroxetine in human colon cancer cells: Involvement of MET and ERBB3. Issue 2 (13th November 2018) - Jang, Won‐Jun; Jung, Sung Keun; Vo, Tam Thuy Lu; Jeong, Chul‐Ho
Abstract: The concept of drug repositioning has recently received considerable attention in the field of oncology. In the present study, we propose that paroxetine can be used as a potent anticancer drug. Paroxetine, one of the selective serotonin reuptake inhibitors (SSRIs), has been widely prescribed for the treatment of depression and anxiety disorders. Recently, SSRIs have been reported to have anticancer activity in various types of cancer cells; however, the underlying mechanisms of their action are not yet known. In this study, we investigated the potential anticancer effect of paroxetine in human colorectal cancer cells, HCT116 and HT‐29. Treatment with paroxetine reduced cell viability, which was associated with marked increase in apoptosis, in both the cell lines. Also, paroxetine effectively inhibited colony formation and 3D spheroid formation. We speculated that the mode of action of paroxetine might be through the inhibition of two major receptor tyrosine kinases – MET and ERBB3 – leading to the suppression of AKT, ERK and p38 activation and induction of JNK and caspase‐3 pathways. Moreover, in vivo experiments revealed that treatment of athymic nude mice bearing HT‐29 cells with paroxetine remarkably suppressed tumour growth. In conclusion, paroxetine is a potential therapeutic option for patients with colorectal cancer.